(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study sought to identify the most common physical gestures used by female student teachers during managing the classroom interaction in the first three grades. The researcher adopted the qualitative research design which suits the nature of the study and the direct observation technique to collect the required data. The study population consisted of 112 students and the sample consisted of 40 female student teachers who were chosen with respect to the purposive method. The findings of the study come as follows: The most common gestures among the individuals of the sample are concluded in three forms of gestures: first, it is negative as the female student teacher is afraid and psychologically stressed. Second, it is positive as the female student teacher smiles at students and tries to communicate with them. Third, it is of a controlled nature of the classroom; frequency percentage ranged between medium to low. This may indicate that female student teachers do not rely mainly on physical gestures during managing the classroom interaction; this may go back to their reliance on other methods to deal with the wrong behaviors in the first three grades. Finally, the study recommended a set of recommendations.